2019
DOI: 10.1080/09640568.2019.1671815
|View full text |Cite
|
Sign up to set email alerts
|

Direct potable water reuse in five arid inland communities: an analysis of factors influencing public acceptance

Abstract: Direct potable reuse (DPR) can improve reliability of water supplies by generating drinking water from wastewater, but communities have consistently opposed DPR more than other forms of reuse. Using interview data regarding DPR projects in five inland communities, this study fills gaps in the literature with an analysis of factors influencing acceptance of DPR. While scholars have recommended public processes used to implement non-potable and indirect potable reuse projects, there is little-to-no documentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…This synthesis shows that while there are general acceptance problems across the globe, the solutions need to be based on scientific evidence collected locally and tailored to local circumstances. Comparative studies of water reuse acceptance have been conducted across different locations in the United States (Hartley 2006;Garcia-Cuerva et al, 2016;Scruggs et al, 2020), Turkey (Buyukkamaci and Alkan 2013) and across different countries (Crampton et al, 2016;Hurlimann and Dolnicar 2016). Single-case studies on local acceptance surveys are also available for comparison of similarities and differences.…”
Section: A Synthesis Of the Reuse Acceptance Enigmamentioning
confidence: 99%
See 1 more Smart Citation
“…This synthesis shows that while there are general acceptance problems across the globe, the solutions need to be based on scientific evidence collected locally and tailored to local circumstances. Comparative studies of water reuse acceptance have been conducted across different locations in the United States (Hartley 2006;Garcia-Cuerva et al, 2016;Scruggs et al, 2020), Turkey (Buyukkamaci and Alkan 2013) and across different countries (Crampton et al, 2016;Hurlimann and Dolnicar 2016). Single-case studies on local acceptance surveys are also available for comparison of similarities and differences.…”
Section: A Synthesis Of the Reuse Acceptance Enigmamentioning
confidence: 99%
“…The acceptance of water reuse cannot be separated from local factors such as the specific potential depending on available water resources, the exposure to certain forms of water reuse and the reuse practicability in terms of associated costs of treatment and distribution. In some regions, some water sources might be more accepted due to scarcity conditions, and awareness of water scarcity can even increase the likelihood of accepting water reuse (Dolnicar et al, 2011;Fielding et al, 2018;Scruggs et al, 2020). In regions of water abundance, some water sources such as desalination might not be accepted.…”
Section: Influence Of Local Resource Types On Acceptancementioning
confidence: 99%
“…However, other recent research in inland parts of the Southwestern United States has shown that, even today, a high level of participation-in the form of delegated power to citizens-is not always required by communities. For example, community smallness, which can facilitate communication and transparency, and lived experience with water scarcity appear to positively influence public attitudes toward potable reuse and might act as substitutes for some of the engagement seen in San Diego (Scruggs et al, 2019).…”
Section: The Importance Of Context and Public Involvement In Decision Makingmentioning
confidence: 99%
“…Millan et al (2015) created written communication plans for engaging the various actors involved in potable reuse projects (a state-level communication plan and a community-level outreach plan) that can be adapted to each community's unique needs and context. The growing body of research on public attitudes toward reuse demonstrates the importance of numerous factors that community officials/entities contemplating reuse should consider, along with examples of successful and unsuccessful strategies for engaging the public on the topic of reuse (Scruggs et al, 2019).…”
Section: The Importance Of Context and Public Involvement In Decision Makingmentioning
confidence: 99%
“…Two notable case studies-in Australia in Toowoomba, Queensland, and in San Diego, Calif.have been described by Hurlimann and Dolnicar (2010) and Trussell et al (2002). As a result, researchers have conducted numerous studies to better understand reasons for public opposition and determine optimal strategies for public education and outreach on the topic of potable water reuse, as summarized by Scruggs et al (2019). However, few studies have focused on arid inland communities, and Ormerod and Scott (2012) and Scruggs et al (2019) have shown that local context matters when it comes to public perceptions of potable reuse.…”
mentioning
confidence: 99%